Digital Innovations in Southeast Asian: Research-Driven Mapping Local Governance for Efficiency and Participation - Hanafi, Sukwan; Nurmandi, Achmad; Lawelai, Herman; Baulete, Elaine; Sohsan, Imron (Universitas Muhammadiyah Tangerang, 2025)
This study addresses issues of bureaucratic inefficiency and low public participation in governance by systematically mapping the scope of digital innovation in local governance throughout Southeast Asia. The research seeks to understand how technology aids governance outcomes, guided by the region’s disparities in digital infrastructure and institutional readiness. The study conducts a systematic literature review of 996 publications from Scopus, following the PRISMA protocol and employing bibliometric analysis via RStudio-Biblioshiny and CiteSpace to derive trends, themes, and gaps concerning Indonesia, Malaysia, Singapore, Thailand, and the Philippines. The results demonstrate and actively reinforce the three dominant innovation clusters: smart cities, e-government systems, and citizen participation platforms that foster greater democratic engagement alongside improved administrative efficiency. The analysis emphasizes the factors critical for successful digital transformation: institutional readiness, digital competency, and cross-organizational collaboration. By synthesizing regional best practices and thematic patterns, the research provides strategic recommendations for policymakers aiming to cultivate flexible, inclusive, and ethically responsible frameworks of implications focused on formulated digital governance. These findings emphasize the need to align technology with community needs and participatory processes, thereby directing further research on interoperability, AI ethics, and public trust in digital public administration.Studi ini membahas masalah ketidak efisienan birokrasi dan rendahnya partisipasi publik dalam tata kelola pemerintahan dengan secara sistematis memetakan ruang lingkup inovasi digital dalam tata kelola pemerintahan di seluruh Asia Tenggara. Penelitian ini bertujuan untuk memahami bagaimana teknologi mendukung hasil tata kelola pemerintahan, dengan mempertimbangkan disparitas infrastruktur digital dan kesiapan institusional di wilayah tersebut. Studi ini melakukan tinjauan literatur sistematis terhadap 996 publikasi dari Scopus, mengikuti protokol PRISMA, dan menggunakan analisis bibliometrik melalui RStudio-Biblioshiny dan CiteSpace untuk mengidentifikasi tren, tema, dan celah terkait Indonesia, Malaysia, Singapura, Thailand, dan Filipina. Hasilnya menunjukkan dan secara aktif memperkuat tiga kluster inovasi dominan: kota pintar, sistem e-pemerintahan, dan platform partisipasi warga yang mendorong keterlibatan demokratis yang lebih besar bersamaan dengan efisiensi administratif yang lebih baik. Analisis ini menyoroti faktor-faktor kritis untuk transformasi digital yang sukses: kesiapan institusional, kompetensi digital, dan kolaborasi lintas organisasi. Dengan mensintesis praktik terbaik regional dan pola tematik, penelitian ini memberikan rekomendasi strategis bagi pembuat kebijakan yang bertujuan untuk mengembangkan kerangka kerja yang fleksibel, inklusif, dan etis dalam tata kelola digital. Temuan ini menekankan pentingnya menyelaraskan teknologi dengan kebutuhan komunitas dan proses partisipatif, sehingga mengarahkan penelitian lebih lanjut pada interoperabilitas, etika AI, dan kepercayaan publik dalam administrasi publik digital.